Rancangan Sistem Pendukung Keputusan “TechTrack” Berdasarkan Evaluasi Kualitas UI UX Aplikasi - Siaka, Made Bayu Maha Krisna; Wibawa, I Gede Arta (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2023)
Smartphone is a portable electronic communication device that enables individuals to engage in various activities, including work, communication, and entertainment. It serves as a versatile tool that can be easily carried and utilized in different locations, providing convenience and facilitating human interactions across multiple domains."TechTrack," is a decision support system for selecting smartphones based on user interface and user experience feasibility. The ever-growing variety and complexity of smartphone models available in the market make it challenging for consumers to make well-informed purchasing decisions.The TechTrack app provides personalized recommendations by considering user preferences, specifications, and reviews. The system underwent usability testing, with the resulting System Usability Scale (SUS) value. The app aims to simplify the decision-making in selecting smartphones by offering comprehensive information, comparison features, user reviews, and a rating system. TechTrack shows potential in enhancing the user experience and helping users in making informed purchasing decisions.